Microglia extracellular vesicles: focus on molecular composition and biological function. (27th August 2021) - Ceccarelli, Lorenzo; Giacomelli, Chiara; Marchetti, Laura; Martini, Claudia
Abstract : Extracellular vesicles (EVs) are a heterogeneous family of cell-derived lipid bounded vesicles comprising exosomes and microvesicles. They are potentially produced by all types of cells and are used as a cell-to-cell communication method that allows protein, lipid, and genetic material exchange. Microglia cells produce a large number of EVs both in resting and activated conditions, in the latter case changing their production and related biological effects. Several actions of microglia in the central nervous system are ascribed to EVs, but the molecular mechanisms by which each effect occurs are still largely unknown. Conflicting functions have been ascribed to microglia-derived EVs starting from the neuronal support and ending with the propagation of inflammation and neurodegeneration, confirming the crucial role of these organelles in tuning brain homeostasis. Despite the increasing number of studies reported on microglia-EVs, there is also a lot of fragmentation in the knowledge on the mechanism at the basis of their production and modification of their cargo. In this review, a collection of literature data about the surface and cargo proteins and lipids as well as the miRNA content of EVs produced by microglial cells has been reported. A special highlight was given to the works in which the EV molecular composition is linked to a precise biological function.